MUSHKILAH AL-AḤĀDĪTH AL-DAKHĪLAH FĪ TAFSĪR AL-QUR’ĀN AL-῾AẒĪM - Mubarok, Abdullah (AL ITQAN: Jurnal Studi Al-Qur'an, 2021)
The Hadith of the Prophet Muhammad is an inseparable relationship with the interpretation of the Qur'an. For this reason, the best product of interpretation is the interpretation of the historical interpretation method. The product of the interpretation of the Qur'an in all of the commentaries turned out to be all found to have sham interpretations, although with different percentages. The biggest problem with this discovery is that the result of interpretation is an understanding that is considered absolute truth for the reader so ignorant teaching becomes a belief that is definitely true. Dakhil in the interpretation is a serious problem that must be resolved because it is considered a barrier to the progress of Islam. Furthermore, Islam will be accused by its enemies of being a religion whose teachings are sourced from lies and superstition. Although the source of interpretation is divided into two, namely the source of the history and the interpreter's mind. This research focuses on Islamic methodology in ensuring that the sources of hadith and history as an inseparable relationship with the Qur'an, are guaranteed authentic and can be accounted for. So this study aims to unravel the problem of dakhil in interpretation that comes from hadith and history. Hadiths and narrations originating from the Prophet Muhammad, companions, tabi'in and the history of Israel have different classifications of status to be used as religious teachings. So that the interpretation of the Qur'an is not always considered as the Qur'an itself.